Multi-Phase Dolomitization in the Jurassic Paleo-Oil Reservoir Zone, Qiangtang Basin (SW China): Implications for Reservoir Development - Hao, Ruilin; Pan, Liyin; Mu, Nana; Li, Xi; Fu, Xiaodong; Xiong, Shaoyun; Liu, Siqi; Zheng, Jianfeng; She, Min; Munnecke, Axel (Minerals, 2024)
The age and dolomitization processes in the Paleo-oil reservoir zone, which is composed of massive dolostones found in the Qiangtang Basin (SW China), are still debated. In this research, the Long’eni-Geluguanna Area was selected. Macroscopic information, thin sections, and geochemical methods were used to investigate the dolomitization characteristics and the processes that controlled dolomitization. Five types of replacive dolomites and two types of dolomite cement were observed. Some of the dolomites displayed ghosts of primary sedimentary structures. Saddle dolomites were prevalent, occurring in the interparticle and moldic pores of the limestone which should have been filled at an early diagenetic stage. Ten microfacies types were identified. The foraminifera assemblage provides evidence that the studied interval is of Early Jurassic age. The δ13C values are similar to the contemporaneous seawater signature. The REE+Y patterns of limestones and dolostones exhibit similarities to that of seawater. The mean Na and Sr values are comparable to those of other near-normal seawater dolomites. The δ18O values of all lithologies are markedly depleted. The dolomitization started penecontemporaneously, with deposition. A general sand shoal setting with patch reefs developed. The dolomitizing fluids, near-normal seawater, was probably formed by slight evaporation on top of the shoal. Saddle dolomites in the interparticle and moldic pores might indicate hydrothermal activity, which also caused the recrystallization of some pre-existing dolomites. The recrystallization might have slightly increased the crystal size, demolished the ghost structures, formed saddle dolomites, and altered the REE+Y patterns. The recrystallization extent diminished with increasing distance from the fluids-providing fracture. Furthermore, the existence of protected areas within the sand shoal settings could enhance the vertical and horizontal heterogeneity of dolostone reservoirs.
CRIS-Team Scopus Importer:2024-10-04
Keywords: dolomitization; dolostone; microfacies analysis; Qiangtang basin; sedimentary environment